Selecting likely causal risk factors from high-throughput experiments using multivariable Mendelian randomization - Verena Zuber (Nature Portfolio, 2020)
Multivariable Mendelian randomization (MR) extends the standard MR framework to consider multiple risk factors in a single model. Here, Zuber et al. propose MR-BMA, a Bayesian variable selection approach to identify the likely causal determinants of a disease from many candidate risk factors as for example high-throughput data sets.